2022
DOI: 10.1039/d2cp00274d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functional substates of KRas during GTP hydrolysis with enhanced sampling simulations

Abstract: As the hub of major signaling pathways, Ras proteins are implicated in 19% of tumor-caused cancers due to perturbations in their conformational and/or catalytic properties. Despite numerous studies, the functions...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 87 publications
(148 reference statements)
2
24
0
Order By: Relevance
“…Ras oncoproteins can exist in different nucleotide-bound and mutant forms in cells, all of which are inherently flexible 7,[29][30][31][32][33]54,55 populating a diverse set of conformations including many that possess druggable pockets unobserved in the ground structures. To date, studies that took advantage of the cryptic pockets 10,[13][14][15]38,56 for targeting have significantly advanced the therapeutics development against Ras and proved covalent modification a feasible strategy for direct inhibition of Ras(G12C)ÁGDP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ras oncoproteins can exist in different nucleotide-bound and mutant forms in cells, all of which are inherently flexible 7,[29][30][31][32][33]54,55 populating a diverse set of conformations including many that possess druggable pockets unobserved in the ground structures. To date, studies that took advantage of the cryptic pockets 10,[13][14][15]38,56 for targeting have significantly advanced the therapeutics development against Ras and proved covalent modification a feasible strategy for direct inhibition of Ras(G12C)ÁGDP.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Conformational exchange was also captured by relaxation-based NMR in the inactive GDP-bound state, which however occurs on a much faster timescale. 28 Previous molecular dynamics and enhanced sampling simulations 7,11,[29][30][31][32][33] suggest that the cryptic pockets can commonly pre-exist in different nucleotide-bound and mutant forms. However, it remains unclear how the mutations and activation states alter the ''invisible'' vulnerable conformers of Ras leading to the differential druggabilities noted in recent drug development efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental structures and computational studies stemming from multiple work teams suggested that G13D mutants in the three isoforms (HRAS, KRAS and NRAS) had an altered active site and conformational changes of the switch domains that affect the stability of the nucleotide-binding pocket [ 8 , 32 , 33 , 34 ]. More previous studies revealed that mutations different from codons 12, 13, and 61 also exerted significant effect on the conformation states of the switch domains and the nucleotide binding [ 12 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Despite these successes, molecular mechanism of mutation-induced conformational state changes of the switch domains from KRAS are still insufficient currently.…”
Section: Introductionmentioning
confidence: 99%
“…59 Markov State Model (MSM) analysis, Replica Exchange MD, and Principal Component Analysis (PCA) have also been applied specifically to K- Ras4B. 47,48,50,53…”
Section: Introductionmentioning
confidence: 99%